2010
DOI: 10.1139/g10-079
|View full text |Cite
|
Sign up to set email alerts
|

SNP discovery by amplicon sequencing and multiplex SNP genotyping in the allopolyploid species Brassica napusThis article is one of a selection of papers from the conference “Exploiting Genome-wide Association in Oilseed Brassicas: a model for genetic improvement of major OECD crops for sustainable farming”.

Abstract: Oilseed rape (Brassica napus) is an allotetraploid species consisting of two genomes, derived from B. rapa (A genome) and B. oleracea (C genome). The presence of these two genomes makes single nucleotide polymorphism (SNP) marker identification and SNP analysis more challenging than in diploid species, as for a given locus usually two versions of a DNA sequence (based on the two ancestral genomes) have to be analyzed simultaneously during SNP identification and analysis. One hundred amplicons derived from expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…The SNPs were chosen to cover a range of the 76 supercontigs on which SNPs were predicted, from the list of 21,814 SNPs described in Zander et al (2013). A designability assessment conducted using the Illumina Assay Design Tool (ADT) scored the 384 SNPs at 0.4 or above, which is deemed a good score for the Illumina GoldenGate assay (Durstewitz et al, 2010). Sample preparation for the Illumina GoldenGate assay was performed according to the Illumina GoldenGate Genotyping Assay guide (According to manufacturer's instructions).…”
Section: Illumina Goldengate Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The SNPs were chosen to cover a range of the 76 supercontigs on which SNPs were predicted, from the list of 21,814 SNPs described in Zander et al (2013). A designability assessment conducted using the Illumina Assay Design Tool (ADT) scored the 384 SNPs at 0.4 or above, which is deemed a good score for the Illumina GoldenGate assay (Durstewitz et al, 2010). Sample preparation for the Illumina GoldenGate assay was performed according to the Illumina GoldenGate Genotyping Assay guide (According to manufacturer's instructions).…”
Section: Illumina Goldengate Assaymentioning
confidence: 99%
“…Previous studies using the Illumina GoldenGate assay have shown that it can be used to reliably score SNPs for genetic analysis (Durstewitz et al, 2010). Furthermore, it is cost-effective and flexible for analysing large numbers of SNPs (Appleby et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many SNPs have been discovered in B. napus [22, 23] and B. oleracea [24]. However, these SNPs are inadequate for large-scale applications [23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to polyploidy, two classes of polymorphisms need to be considered. Sites that are polymorphic between accessions represent the so-called intragenomic SNPs [23] that are especially versatile for genetic mapping and discrimination of accessions. Large SNP collections have been put together for Brassica napus [2426].…”
Section: Introductionmentioning
confidence: 99%
“…Large SNP collections have been put together for Brassica napus [2426]. SNPs that differentiate between the homoeologous A and C genomes were termed interhomoeolog polymorphism [24] or intergenomic SNP [23]. This SNP class proved to be valuable for the screening of BAC libraries, since intergenomic SNPs identify and at the same time differentiate homoeologous sequences [21].…”
Section: Introductionmentioning
confidence: 99%